SYSTEMATIC FORMULATION OF HIGH PERFORMANCE CONCRETE PAVEMENT - Salil Kumar Roy; Handoko Sugiharto; Anton Kristando; Salim Himawan S (Civil Engineering Dimension, 2005)
Following a 25-1 fractional factorial design concept, an experiment was planned ; sixteen experimental mixes were calculated from a basic mix (cement : sand : aggregates : fly ash = 1 : 1.3 : 2.6 : 0.8 and W/C ratio of 0.37) and determined changes (cement = 0.1 ; sand = 0.1 ; aggregates = 0.2 ; fly ash = 0.04 and changing W/C ratio by 0.01) using Taguchiâs orthogonal array. Samples were made from each data point. Compressive strength and water absorption were determined after each of two curing conditions (a) 28 days in the water, (b) 28 days in the water and 32 days in the air after that. Mix no 12 [Cement : Sand : Gravel : Fly Ash = 0.9 : 1.2 : 2.8 : 0.76] was found to have highest compressive strength and lowest water absorption.